2014
DOI: 10.3762/bjoc.10.5
|View full text |Cite
|
Sign up to set email alerts
|

Silica: An efficient catalyst for one-pot regioselective synthesis of dithioethers

Abstract: SummaryThe development of a silica-promoted highly selective synthesis of 1,2 or 1,3-dithioethers via solvent-free one-pot tandem reactions of an allyl bromide with excess thiol at room temperature is described. The choice of silica gel, either pre-calcined or moistened with water, exhibited notable regioselectivity in the formation of dithioethers. Plausible mechanistic routes were explored and postulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Kundu and co‐workers described the selective synthesis of 1,2‐dithioethers 151 and 1,3‐dithioethers 152 via solvent‐free and metal‐free one‐pot tandem reactions of allyl bromide 153 a with an excess of the thiol 3 (Scheme ). When dry, pre‐calcinated silica gel is used, 1,2‐dithioethers 151 (the Markovnikov adducts) are exclusively obtained after 6–10 h of reaction in 65–91 % yields.…”
Section: Synthesis Of Chalcogen Ethersmentioning
confidence: 99%
“…Kundu and co‐workers described the selective synthesis of 1,2‐dithioethers 151 and 1,3‐dithioethers 152 via solvent‐free and metal‐free one‐pot tandem reactions of allyl bromide 153 a with an excess of the thiol 3 (Scheme ). When dry, pre‐calcinated silica gel is used, 1,2‐dithioethers 151 (the Markovnikov adducts) are exclusively obtained after 6–10 h of reaction in 65–91 % yields.…”
Section: Synthesis Of Chalcogen Ethersmentioning
confidence: 99%
“…The same authors also utilized the catalytic activity of SiO2 NPs in the bis-Michael addition of active methylene compounds to conjugated alkenes, 275 which was considered possible only with a few catalysts, like ruthenium complex 276 and basic ionic liquid catalyst 277,278 . Kundu et al 279 reported using a commercial silica gel for dithioethers synthesis. By controlling the moisture level of the silica gel (dry/moistened), the authors were able to conduct the regioselective synthesis of 1,2-and 1,3-dithioethers at room temperature by reacting a variety of aromatic thiols with alkyl bromide.…”
Section: Catalytic Activities Of Silica Nanoparticlesmentioning
confidence: 99%